2014
DOI: 10.1007/s10869-014-9350-0
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling in the Selection Interview? How Applicants Respond to Past Behavior Questions

Abstract: Purpose Increased use of past behavior questions makes it important to understand applicants' responses. Past behavior questions are designed to elicit stories from applicants. Four research questions were addressed: How do applicants respond to past behavior questions, in particular, how frequent are stories? When applicants produce stories, what narrative elements do they contain? Is story production related to applicants' characteristics? Do responses affect interview outcomes? Design/Methodology/Approach U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 47 publications
3
49
0
Order By: Relevance
“…Given that past-behavior questions project narrative responses, one might expect that candidates most often respond to them by telling stories. There are little data on this issue, but one study found that in fact only 23% of responses to past-behavior questions are stories (Bangerter, Corvalan, & Cavin, 2014). Two main problems could prevent candidates from producing narrative responses.…”
Section: This Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Given that past-behavior questions project narrative responses, one might expect that candidates most often respond to them by telling stories. There are little data on this issue, but one study found that in fact only 23% of responses to past-behavior questions are stories (Bangerter, Corvalan, & Cavin, 2014). Two main problems could prevent candidates from producing narrative responses.…”
Section: This Studymentioning
confidence: 99%
“…We reanalyzed the data by measuring candidates' pause durations between recruiters' question offset and candidates' response onset and using them as predictors of response type (Research Question 1) and recruiter hiring recommendations (Research Question 2). In investigating Research Question 2 we controlled for a range of ancillary variables (e.g., personality, general mental ability [GMA], and the like) using data available from the original study and from Bangerter et al (2014), who investigated the impact of different response types on hiring recommendations controlling for the abovementioned ancillary variables and found that response types influenced hiring recommendations, for example, narrative responses were associated with better hiring recommendations. Research Question 2 goes beyond Bangerter et al (2014) by controlling for the same ancillary variables and response type to test the additional effect of delays.…”
Section: This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The BDI is unique among interview types given its exclusive focus on description of past experiences, responses that should be more extensive and verbally involved given that they typically include a description of the context and the problem, the actions taken, and the outcome of those actions. Some have even described the BDI process as akin to storytelling (Bangerter, Corvalan, & Cavin, 2014). Being talkative and gregarious (the sociability aspect) by itself should not necessarily translate into more effective reporting of experiences and, in fact, could be counterproductive.…”
Section: Personnel Assessment and Decisionsmentioning
confidence: 99%